Barriers and facilitators in supporting people with intellectual disability to report sexual violence: perspectives of Australian disability and mainstream support providers. Issue 1 (12th February 2018) - Fraser-Barbour, Ellen Frances; Crocker, Ruth; Walker, Ruth
Abstract : Purpose: Evidence from Australia and worldwide has highlighted the ongoing marginalisation, discrimination, abuse, violence and neglect of people with disability. One of the main areas of concern is that despite such evidence there remain fundamental barriers for people with disability to report violence and/or access supports. Significantly few studies have canvased the perspectives of people with intellectual disability (ID), family members or disability service providers. Accordingly as a first step, the purpose of this paper is to explore the perceptions of disability and violence-response professionals' regarding the barriers and facilitators of effective support for people with ID reporting sexual violence and accessing mainstream supports. Design/methodology/approach: A qualitative research design informed the basis of this study. Semi-structured interviews were conducted with seven participants who held roles within disability services and mainstream violence response. Interviews were recorded and transcribed. These transcripts were then analysed individually using a combination of thematic analysis and discourse analysis to bring to light the social and material structures within service systems in terms of how they disempower or empower supports for people with ID. Findings: Participants from both services reported that professionals (particularly those outside the disability sector) lacked awareness of practical ways in which they could support people with ID to report and access services outside of disability-specific services. Participants also felt the capacity for people with ID to have a voice about what happens in the "aftermath" of reporting sexual violence was rarely acknowledged. Participants called for education and development of resources which could guide professional practice across disability and wider violence-response services. Participants saw investment in building interagency relationships across sectors as key to supporting the citizenship of people with ID. Originality/value: This study suggests that there is a strong need for better community engagement and understanding of the multi-faceted issues surrounding responses to violence concerning people with ID. The findings of this study also outline implications for practice and policy which may be of interest to professionals both within disability and wider violence-response sectors in Australia and internationally.